Penyuluhan Penganggaran untuk Wirausaha pada Anggota Kelompok Mujur Fish Farm di Dusun Brengosan, Sleman, Yogyakarta - Bhenu Artha; Antonius Satria Hadi; Bahri Bahri; Ardhi Khairi; Niken Permata Sari (Humanis, 2022)
This community service activity to give counseling to fish farmer groups in Dusun Brengosan, Donoharjo Village, Ngaglik, Sleman, Yogyakarta Special Region which aims to provide additional understanding and knowledge to the fish farmer group "Mujur Fish Farm" about financial budgeting. The community service activity aims to increase understanding and additional knowledge to the “Mujur Fish Farm” fish farmer group in Donoharjo Village about financial budgeting which is carried out using lecturing, demonstrating, and question & answer methods. The benefits that participants can get from this community service activity include increasing knowledge, understanding, and experience of the "Mujur Fish Farm" fish farmer group in Donoharjo Village about financial budgeting.